Characterisation of the H5 and N1 genes of an Indonesian highly pathogenic Avian Influenza virus isolate by sequencing of multiple clone approach - Hartawan, Risza; Robinson, Karl; Mahony, Timothy; Meers, Joanne (Indonesian Journal of Animal and Veterinary Sciences, 2010)
Hemagglutinin and neuraminidase are the main antigenic determinants of highly pathogenic avian influenza (HPAI) virus. The features of these surface glycoproteins have been intensively studied at the molecular level. The objective of this research was to characterise the genes encoding these glycoproteins by sequencing of multiple clones. The H5 and N1 genes of isolate A/duck/Tangerang/Bbalitvet-ACIAR-TE11/2007 were each amplified in one or two fragments using reverse transcriptase-PCR (RT-PCR), and subsequently cloned into pGEM-T Easy TA cloning system. The sequencing result demonstrated high homology between respective clones but with several variations that were identified as single nucleotide polymorphisms (SNPs). A total of 1,707 base pair and 1,350 base pair of H5 and N1 genes respectively were successfully assembled from multiple clones containing the genes of interest. The features of both H5 and N1 genes from this isolate resemble the typical characteristics of Indonesian strains of H5N1 virus from sub-clade 2.1.3. Key Words: Avian Influenza, Characterization, Gene Cloning, Hemagglutinin, Neuraminidase